A Compact Ultra-Wideband Band-Notched Monopole Microstrip Antenna with Modified Complementary Split Ring Resonator - Jiang, Di; Huang, Tao; He , Zhaosheng (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A simple and compact microstrip ultra-wideband printed monopole antenna with filtering characteristic is presented. The proposed antenna comprises of a wave ground structure and a swallow radiating patch with co-directional modified pentagon complementary split-ring resonators, which are notched by altering three parameters, respectively. By using a modified wave ground structure, impedance matching characteristic that involves operating frequency band of C-band satellite communication systems and WLAN is obtained. The designed antenna has a compact size of 25×27.9 mm2 and provides the impedance bandwidth of more than 137% from 2.2 GHz to 11.8 GHz, with notch frequency band at 3.59-4.255 GHz, 5.12-5.41 GHz and 5.69-6.03 GHz. The antenna demonstrates omnidirectional and stable radiation patterns across all the relevant bands. Moreover, a prototype of the proposed antenna is fabricated and the measured results are shown to be in good agreement with the simulated results.